2021
DOI: 10.3390/ijms22126233
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Exopolysaccharides: Genetic Regulation of Their Synthesis and Relevance in Symbiosis with Legumes

Abstract: Rhizobia are soil proteobacteria able to engage in a nitrogen-fixing symbiotic interaction with legumes that involves the rhizobial infection of roots and the bacterial invasion of new organs formed by the plant in response to the presence of appropriate bacterial partners. This interaction relies on a complex molecular dialogue between both symbionts. Bacterial N-acetyl-glucosamine oligomers called Nod factors are indispensable in most cases for early steps of the symbiotic interaction. In addition, different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 185 publications
(325 reference statements)
0
33
0
Order By: Relevance
“…In rhizobia inducing determinate nodules, EPS mutants still induce effective nodules, with EPS playing a signaling role at the late stages of both infection thread initiation and bacterial release ( Kelly et al, 2013 ). However, in symbioses forming indeterminate nodules, EPS is absolutely essential for a successful interaction (reviewed by Fraysse et al, 2003 ; Acosta-Jurado et al, 2021 ). EPS-altered mutants (exhibiting conserved LPS) generated in an isogenic strain, R. loti PN184, able to nodulate Lotus pedunculatus (determinate nodules) and Leucaena leucocephala (indeterminate nodules) showed that they were fully effective on a determinate-nodulating host but ineffective on the indeterminate one ( Hotter and Scott, 1991 ).…”
Section: Types Of Competition and Genetic Features Influencing Competitivenessmentioning
confidence: 99%
“…In rhizobia inducing determinate nodules, EPS mutants still induce effective nodules, with EPS playing a signaling role at the late stages of both infection thread initiation and bacterial release ( Kelly et al, 2013 ). However, in symbioses forming indeterminate nodules, EPS is absolutely essential for a successful interaction (reviewed by Fraysse et al, 2003 ; Acosta-Jurado et al, 2021 ). EPS-altered mutants (exhibiting conserved LPS) generated in an isogenic strain, R. loti PN184, able to nodulate Lotus pedunculatus (determinate nodules) and Leucaena leucocephala (indeterminate nodules) showed that they were fully effective on a determinate-nodulating host but ineffective on the indeterminate one ( Hotter and Scott, 1991 ).…”
Section: Types Of Competition and Genetic Features Influencing Competitivenessmentioning
confidence: 99%
“…Furthermore, they have an important role in crop rotation and are used for production of wood, tannins, oils, dyes, and medicines and in the horticultural trade 1 , 5 . Most species of Fabaceae plants can establish nitrogen-fixing symbioses with soil bacteria, collectively known as rhizobia 6 , 7 . This process, called biological nitrogen fixation (BNF), is an ecological and low-cost alternative providing nitrogen to legume crops.…”
Section: Introductionmentioning
confidence: 99%
“…For example, obligate mycorrhizal fungi respond to lipids and sugars with proliferation and pre-spore formation, and rhizobia bacteria respond to dicarboxylates such as succinate and malate from legume hosts during nodulation and nitrogen fixation (27)(28)(29)(30)(31). Furthermore, features of bacterial nodulation such as extracellular polysaccharide production, malate metabolism, and oxygen sensing are shared with fungal tumor formation (32,33). The response to defined combinations of nutrients may therefore be a general theme in plant-microbe interactions.…”
Section: Mitochondrial Functions and Oxygen Influence Biotrophymentioning
confidence: 99%